Benefits of modern biotechnology in the resistance of hard yellow maize (Zea mays L.) to Spodoptera frugiperda - Reyna-Delgado, Nila-Alexandra (2025)
Hard yellow maize is the most important grain worldwide, as it is a key source of food for chickens and pigs, providing essential protein for humanity. This study evaluates the benefits of releasing seeds of genetically modified hard yellow corn (MADBt), resistant to codling moth (Spodoptera frugiperda), in Los Ríos, Ecuador. To analyze the economic benefits to producers, partial budget models that provide the change in producer margin and the marginal cost benefit were used. To measure the improvement in social welfare, the surplus change model was used. In addition, risks associated with agricultural production were incorporated through Monte Carlo simulations using @Risk software. Information on costs, production and prices was obtained through a survey of producers in Los Ríos. It is concluded that (i) producers benefit from a Marginal Cost Benefit ratio of 1,09 and an increase in margin of US$ 332,36 per hectare; (ii) Ecuadorian society benefits with changes in Social Surplus from the use of MADBt seed, reaching an average expected value of US$ 862 million, distributed between producers (US$ 571 million) and consumers (US$ 291 million); and (iii) the Ecuadorian state also benefits, with a Net Present Value (NPV) of US$ 321 million. It is recommended to evaluate ex-ante the seeds of other genetically modified crops.